Analisis Pengaruh Pertumbuhan Ekonomi Terhadap Degradasi Lingkungan di Indonesia - Dinilhaq, Wafi; Azhar, Zul (Universitas Negeri Padang, 2024)
This study aims to determine and analyze the effect of economic growth on environmental degradation in Indonesia. This study uses secondary data sourced from the World Bank and Global Carbon Project (GCP) with research variables divided into two parts, namely the bond variable which in this study is defined as environmental degradation and the independent variable consisting of economic growth , population density, energy consumption and trade linkages. This study uses multiple regression analysis. The results of this study reveal that: (1) Economic growth has a positive and significant effect on environmental degradation in Indonesia. (2) Population density has a positive and significant effect on environmental degradation in Indonesia. (3) Energy consumption has a positive and insignificant effect on environmental degradation in Indonesia. (4) Trade openness has a positive and insignificant effect on environmental degradation in Indonesia (5) Economic growth, population density, energy consumption and emergence of trade have a simultaneous effect on environmental degradation in Indonesia.